Expression Profiles of Matrix Metalloproteinases and Their Inhibitors in Nasal Polyps - Duan C; Yu X; Feng X; Shi L; Wang D (Dove Medical Press, 2024)
Chen Duan,1 Xuemin Yu,2 Xin Feng,1 Li Shi,3 Deyun Wang4 1Department of Otorhinolaryngology, Qilu Hospital of Shandong University, National Health Commission (NHC) Key Laboratory of Otorhinolaryngology, Shandong University, Jinan, Shandong, 250000, People's Republic of China; 2Department of Otorhinolaryngology, Qilu Hospital (Qingdao), Cheeloo College of Medicine, Shandong University, NHC Key Laboratory of Otorhinolaryngology (Shandong University), Qingdao, Shandong, 250000, People's Republic of China; 3Department of Otolaryngology, The Second Hospital of Shandong University, Jinan, Shandong, 250000, People's Republic of China; 4Department of Otolaryngology, Yong Loo Lin School of Medicine, National University of Singapore, Singapore, SingaporeCorrespondence: Li Shi, Department of Otolaryngology, The Second Hospital of Shandong University, Jinan, Shandong, 250000, People's Republic of China, Email shili126@sina.com Xin Feng, Department of Otorhinolaryngology, Qilu Hospital of Shandong University, National Health Commission (NHC) Key Laboratory of Otorhinolaryngology, Shandong University, Jinan, Shandong, 250000, People's Republic of China, Email drfengxin@sdu.edu.cnPurpose: Nasal polyp (NP) is characterized by inflammation of the sinonasal mucosa with predominant inflammatory cell infiltration. Matrix metalloproteinases (MMPs) and tissue inhibitor of metalloproteinases (TIMPs) are recognized to play an important role in leukocyte migration in airway inflammation. Herein, efforts were made to confirm the expression levels of MMPs/TIMPs and study the relationship between the infiltration of inflammatory cells and local expression levels of MMPs/TIMPs in NPs.Patients and Methods: NP tissues were obtained from 42 Chinese patients with bilateral nasal polyps during the endoscopic sinus surgery. Inferior turbinate (IT) tissues from 19 patients with septal deviation were taken during the rhinoplasty surgery as controls. mRNA and protein levels of MMP1, MMP9, MMP10, MMP12, TIMP1 and TIMP3 were assessed by quantitative PCR and immunohistochemistry.Results: Eosinophilia (72%, 23/32 samples), neutrophilia (41%, 13/32 samples), and increase in macrophages (38%, 12/32 samples) were found in NP tissues. mRNA expression of MMP1 (10.9-fold), MMP9 (4.1-fold), MMP10 (6.7-fold) and MMP12 (3.5-fold) were significantly up-regulated, while TIMP1 (1.5-fold) and TIMP3 (6.0-fold) were significantly down-regulated in NPs (n=42) as compared to the controls (n=19). The immunostaining levels of all 4 MMPs and two TIMPs were higher in NPs than those in controls. The co-localization of MMP1/MMP10/MMP12 and macrophages were identified in NPs. MMP9 was mainly expressed in neutrophils, while TIMP1 or TIMP3 were mostly found in eosinophils in NPs.Conclusion: The results of our study indicate that tissue remodeling is significant in NPs, where MMPs/TIMPs play important roles in both tissue remodeling and inflammatory cells infiltration.Keywords: remodeling, inflammatory cells, extracellular matrix, matrix metalloproteinases